The Role of Social Science Education in Shaping Student Understanding of Society - Usman Hidayat; Ratna Kurniati Wulandari (Journal of Smart Pedagogy and Education, 2025)
This study investigates the impact of reinstating high school tracking for the 2025/2026 academic year on social science education in Indonesia. Amidst digital saturation and declining PISA 2022 scores, the research employs a qualitative meta-synthesis of recent educational policies and literacy indices. Findings indicate that while tracking addresses academic continuity, it fails to inherently resolve crises in critical thinking or misinformation vulnerability. The study proposes a framework integrating digital citizenship and critical pedagogy, leveraging the Indonesian guyub culture through the Collective Resonance Communication Model (CRCM). This approach transforms social science from rote memorization into a mechanism for navigating the post-truth public sphere. Ultimately, the effectiveness of social science education depends on fostering social intelligence and ethical agency. By bridging national identity with global digital engagement, this framework equips students to address complex social problems. The research concludes that systemic pedagogical shifts are vital for achieving the visionary Golden Indonesia 2045.